Comparative Analysis of Nutritional Content of Mudskipper Periophthalmus variabilis and Boleophthalmus boddarti - Saifullah Hidayat; Andi Muhammad Yusuf; Hamdan Hadi Kusuma (UIN Sunan Gunung Djati Bandung, 2022)
Gelodok or mudskipper fish are unique fish that have the ability to live in both aquatic and terrestrial areas. Some Indonesian who live in coastal areas use this fish for consumption. Types of mudskipper that are abundant in Indonesia are from the genera of Boleophtalmus, Periophthalmodon and Periophthalmus, where not all types have been studied for their nutritional content. The aim of this study was to analyze the content of Boleophthalmus boddarti and Periophthalmus variabilis. his study compared the nutritional content of the two types sampled from the Kaliwungu Kendal mangrove ecosystem and the Wedarijaksa Pati mangrove ecosystem. The two types of fish sampled were measured by morphometry which included body length, body width and body weight. Then the fish were analyzed for their nutritional content, namely carbohydrates using the Luff Schroorl test method, protein using the Kjeldahl method, fat using the Soxhlet method, iron using the AAS method, and phosphorus using the spectrophotometer method. The results showed that B. boddarti had a higher protein and iron content than P. variabilis . Meanwhile, P. variabilis had higher carbohydrate, fat and phosphorus content than B. boddarti. The difference was due to different feeding behavior, habitat, and types of food in B.boddarti and P. variabilis.